Body Speech and Cixous, Shelley and Queizán - Fente, Elvira (Madrygal. Revista de Estudios Gallegos, 2015)
We aim to display the analogies between the work of Hélène Cixous, Mary Shelley and feminist thought of María Xosé Queizán. We will try to understand the meaning of woman’s body and how Cixous and Queizán identify it with the word. We will see how Queizán is inspired by Mary Shelley´s work, Frankenstein specifically, to understand motherhood. When the reproducers bodies will be replaced by machines we will achieve, says Queizán, the true equality.